Legal Politics of Intellectual Property Rights Enforcement in Encouraging Investment and Innovation: Implementation Study in Indonesia - Avilla Deva Aryanda; Ali Masyhar (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2025)
Intellectual property rights play an essential role in advancing and improving investment activities in Indonesia. Investment activities can develop rapidly with the existence of intellectual property rights that have the aim of providing legal protection and legal certainty for these investment activities. In this scientific article, two legal problems will be explained, namely, among others, regarding the enforcement of intellectual property rights in encouraging investment and innovation activities in Indonesia and regarding the legal political strategy in balancing the interests of holders or owners of intellectual property rights in investment activities and public interests. In writing this scientific article, the author uses a type of research in the form of normative research using various legal materials to produce various arguments, concepts, and new theories that can later resolve existing legal problems. Then, in this scientific article, two research results will also be explained regarding two existing legal problems, namely, among others, trademark enforcement which has a function as a differentiator for various investment products, and copyright, and patent enforcement which has a function as a potential asset of intangible objects and regarding the protection of intellectual property rights by providing exclusive rights to holders or owners of intellectual property rights but still paying attention to the public interest in encouraging investment and innovation activities in Indonesia.